2012
DOI: 10.21825/af.v25i1.4963
|View full text |Cite
|
Sign up to set email alerts
|

Beyond vegetative propagation of indigenous fruit trees: case of Dacryodes edulis (G. Don) H. J. Lam and Allanblackia floribunda Oliv.

Abstract: Indigenous fruits/nuts of Africa's humid tropics are increasingly being recognized for their contribution to food security, health (nutrition/medicine), income generation, employment and environmental benefits. However, cultivation of the trees yielding these fruits/nuts is constrained by lack of improved planting materials that are true-to-type and have a short enough juvenile phase to fruit production. In addition, information on both above and belowground growth attributes of these species is scarce. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…These techniques can help clone elite specimens and avoid the long juvenile periods from seeds [81]. Under domestication, and in response to purposeful man-led selection, species like D. edulis have reduced juvenile phase, larger fruit size, extended fruiting season, more complementary rooting system if intercropped in agroforestry context with companion crops and are significant carbon sinks within the production system [83]. Farmers in southern Africa deliberately maintain indigenous fruit trees on their farms mainly for their fruits and nuts [84].…”
Section: Domestication Of Indigenous Fruit and Nut Treesmentioning
confidence: 99%
See 2 more Smart Citations
“…These techniques can help clone elite specimens and avoid the long juvenile periods from seeds [81]. Under domestication, and in response to purposeful man-led selection, species like D. edulis have reduced juvenile phase, larger fruit size, extended fruiting season, more complementary rooting system if intercropped in agroforestry context with companion crops and are significant carbon sinks within the production system [83]. Farmers in southern Africa deliberately maintain indigenous fruit trees on their farms mainly for their fruits and nuts [84].…”
Section: Domestication Of Indigenous Fruit and Nut Treesmentioning
confidence: 99%
“…Most African native fruit species have not been brought up to their full potential in terms of quality breeding and selection, scale of production and distribution, value addition and availability [80,83]. The potentials in recurrent selection programmes for breeding of indigenous fruit trees are limited by the relatively long expected time until first fruiting for many of the species [80].…”
Section: Domestication Of Indigenous Fruit and Nut Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…All these factors may in one way or the other play a part in the success rate of grafting and further studies are needed to determine which are the most important. For instance, Asaah et al (2012) found side tongue grafting to be the most appropriate grafting method for Allanblackia floribunda.…”
Section: Effect Of Grafting Techniques On the Propagation Of G Lucidmentioning
confidence: 99%
“…However, dependence on seed may not be the best solution from the farmer's point of view as seed progeny can be highly variable and also have long emergence periods so there is significant time delay before being able to harvest useful products. Vegetative propagation, on the other hand, may lead to low genetic variability but yield offspring that are highly precocious and enable farmers to access products within a short timescale (Akinnifesi et al 2008;Hartmann et al 2011;Asaah et al 2012).…”
Section: Introductionmentioning
confidence: 99%